REACTION OF SOCIETY IN PERSPECTIVE OF CRIMINOLOGY CONCEPTION FOR CRIME PREVENTION - Faisol Azhari (Unissula, 2011)
The prevention of crime is also explained by Criminology. So that Criminology is also include the study of the reaction of society against crime. It might be argued that this belongs, strictly speaking to the domain of sociology of the criminal law but it has to be admitted that the reaction of the state which is the subject matter of penology. They are both strongly by criminogenic forces and should therefore be studied by criminologist. Edwin H Sutherland and Cressey said that the prevention of crime or the reaction of society against crime include within criminology scope the processes of making laws of breaking laws and of reacting toward the breaking laws.The reraction of society against crime include to critize the punitifly of the social reaction and the treatment of raection of society against crime. The reaction of society against crime is also about social perseption about social order and development of perseption of society for social order is depent on development of society which consist of traditional society and modern society.Keyword : Concept of Crime prevention, Reaction of society against crime